Estratégias de comercialização do peixe oriundo da piscicultura familiar do município de Itapecuru-Mirim para mercados institucionais com vistas à garantia do desenvolvimento sustentável - Pinheiro, Míryan Fabianny Nunes (2023)
The modernization of Brazilian agriculture implemented in the 1970s prioritized large-scale production, neglecting the importance of family farmers. From the 1990s onwards, mainly as a result of pressure and struggles from social movements and institutional changes, family farming began to integrate several public policies aimed at the category as an alternative for inclusive and sustainable economic and social development. In this new scenario, the Food Acquisition Program (PAA) was created and institutionalized, aimed at the institutional commercialization of products from family agricultural production. In this context, the objective was to develop marketing strategies for fish from family aquaculture in the municipality of Itapecuru-Mirim for institutional markets with a view to guaranteeing sustainable development. To this end, the study was divided into six stages: (i) documentary bibliographic research; (ii) interviews to assess family fish farmers’ perception of the PAA and its results; (iii) assessment of the productive organization of family aquaculture farmers; (iv) technological innovation; (v) food and nutritional security; (vi) and, promotion of public policies. For the documentary bibliographic research, reports from the Municipal Department of Agriculture of Itapecuru Mirim - MA were accessed, referring to the years 2010 to 2020. The data evaluated were: [modality of PAA in the municipality, producer centers and farmers supplying the PAA (quantity, gender of farmers and activity performed), food produced, production in kilos and institutions benefited]. To understand fish farmers' perception of the PAA and its results, 84 family farmers from 10 rural production centers that participated in the PAA were interviewed using a questionnaire composed of seven dimensions (income, housing, production, food security, political organization, migration and obstacles), from which indicators were created to <measure= them. The productive organization (third stage of the study) occurred through the mobilization of family fish farmers, execution of training and consultancy in enterprise management in which the conceptual and applied bases of <associativism and rural cooperativism were worked on, as a stimulus for collective organizations in the field=, in the form of an Open and Massive Online course and an E-book. In the fourth and fifth stages, the generic blueprint of a family agribusiness was presented to the Municipality's Agriculture Department as a way of enabling the implementation of a fish and fish products processing unit to obtain refrigerated whole fish, steaks and fillets. In the sixth stage of the work, meetings were held with the Municipality's Departments of Education and Agriculture to raise awareness among managers about the importance of purchasing products to be prepared by family fish farmers. With the survey carried out, 21 production centers located in the rural area of the Municipality were quantified, formed by women, agrarian reform settlers, quilombolas, fishermen, aquaculturists and family farmers. Of the 538 family farmers who were members of the PAA over the 11 years of the survey, 505 were female and 33 were male. There was a predominance of products of plant origin (fresh and processed) in the Program, with a total production of 1.456.233 kilos of food, movement of the local economy with the allocation of R$ 5.130.076.25 and the direct processing of six registered social assistance entities that received and passed on food to families in situations of food vulnerability who began to have an increase in their daily diet. The interviews made it possible to demonstrate, based on the interviewees' perception, that the PAA provided benefits to family fish farmers in the seven dimensions researched. Obstacles to its operationalization, such as delays in paying for purchases, can be resolved by adapting the Program to its local context, without compromising the operationalization of this social policy in the evaluated Municipality. It is concluded that the PAA constitutes a driving public policy for the inclusion of Itapecuruense farmers in the institutional market, as the Program contributes to the insertion and guarantee of a market for family farming products through institutional purchases. Furthermore, the PAA in Itapecuru - MA acts positively on the following fronts: food security for individuals in vulnerable situations; improving quality of life; increase in income; greater variety, quantity and quality of food produced; appreciation of local eating habits and short marketing circuits; and, encouraging people to stay in rural areas. In general, the PAA favors, in the Municipality, the recognition of family farmers as a social category and agricultural producer. It is expected that the products generated (online course and E-book) due to their didactic and guiding nature, together with the training of family fish farmers, technological innovation and food and nutritional security will increase the participation of the public evaluated in the Fish Acquisition Program. Food in Itapecuru Mirim - MA.